Refleksi Implementasi Kebijakan Pendekatan Pembelajaran Mendalam di Sekolah Dasar: Studi Literatur tentang Harapan, Tantangan, dan Solusi - Sumilat, Juliana M.; Samauling, Yeci J.; Maay, Meske M.; Tapemo, Melidayanti; Somba, Mega I.; Tomme, Reti J. (Peneliti.net, 2025)
Deep learning has become a strategic approach to improving the quality of basic education in Indonesia, particularly in developing students’ critical thinking, conceptual understanding, and socio-emotional skills. However, recent studies show that learning practices in elementary schools are still dominated by rote memorization with limited student engagement, resulting in shallow and short-lasting understanding. This article presents a comprehensive literature review on the implementation of deep learning in elementary schools by examining its concepts, practices, challenges, and solutions based on research from the past five years. Thematic analysis of open-access scholarly articles indicates that deep learning enhances students’ analytical abilities, learning motivation, and active participation through mindful, meaningful, and joyful learning experiences. These practices are supported by strategies such as thematic projects, scientific discussions, authentic assessments, and the use of adaptive learning technologies. Nevertheless, implementation in real settings continues to face obstacles, including low pedagogical literacy among teachers, limited facilities, administrative burdens, curriculum misalignment, and unequal access to technology. The study emphasizes that successful deep learning implementation requires systemic support, including continuous professional development for teachers, adequate infrastructure, assessment reform, and collaboration among stakeholders. This review is expected to provide a strategic foundation for schools and policymakers in strengthening contextual and sustainable deep learning practices in Indonesian elementary education.